Visible-light photoredox catalysis enabled bromination of phenols and alkenes - Zhao, Yating; Li, Zhe; Yang, Chao; Lin, Run; Xia, Wujiong (Beilstein Journal of Organic Chemistry, 2014)
A mild and efficient methodology for the bromination of phenols and alkenes has been developed utilizing visible light-induced photoredox catalysis. The bromine was generated in situ from the oxidation of Br− by Ru(bpy)33+, both of which resulted from the oxidative quenching process.
Keywords: alkenes; bromination; phenols; photoredox catalyst; visible light